Obligation to do as a regulatory sanction in Brazil: Application to the telecommunications sector - Freitas, Luciano Charlita de; Moura Filho, Ronaldo Neves de; Stanzani, Juliano; Moreira, Renata Machado; Moraes, Leonardo Euler de (Law, State and Telecommunications Review, 2019)
Purpose ”“ This article approaches the legal and economic dimensions of the fine and the so-called obligation to do as alternative sanction methods within the Brazilian regulatory framework and the latter´s relative potentials regarding the full exercise of economic functions by the regulator. Furthermore, it highlights the relative advantages and challenges of the obligation to do and how it can maximize the allocative efficiency of administrative sanctions. Methodology/approach/design ”“ A critical analysis of a pioneering application of the obligation to do, carried out by the telecommunication’s regulatory agency, allows to elucidate the essential requirements for its use and governance. Findings ”“ Conclusions suggest that the obligation to do allows the fulfillment of the allocation, stabilization and distribution functions by regulator while potentially increasing both the society expectation towards sanctioning and investment in the sector. Originality ”“ It presents a pioneering perspective on the exercise of the obligation to do as sanction in the Brazilian telecommunications sector.